2014
DOI: 10.1016/j.jvs.2014.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Atherosclerosis Among 65-year-old Swedish Men — A Population-based Screening Study

Abstract: Objective: There are limited contemporary epidemiological data on the prevalence of carotid atherosclerosis in the general population. The aim was to determine the prevalence of and risk factors associated with carotid artery atherosclerosis among 65-year-old men. Methods: This was a population-based screening study. All 65-yearold men in the County of Uppsala, Sweden, who attended screening for abdominal aortic aneurysm (AAA) 2007e2009, were invited for duplex scanning of the carotid arteries. Results: Of 480… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 0 publications
0
15
0
2
Order By: Relevance
“…However, as not all patients had optimal CV treatment, the rate of CV events could be further reduced in the population studied herein. Another aspect to consider is that the cohort included a low rate of significant carotid stenosis as observed elsewhere [28,29,39,40], and we cannot exclude a link between CV risk of carotid atherosclerosis for patients with stenosis > 50% or >70%.…”
Section: Discussionmentioning
confidence: 99%
“…However, as not all patients had optimal CV treatment, the rate of CV events could be further reduced in the population studied herein. Another aspect to consider is that the cohort included a low rate of significant carotid stenosis as observed elsewhere [28,29,39,40], and we cannot exclude a link between CV risk of carotid atherosclerosis for patients with stenosis > 50% or >70%.…”
Section: Discussionmentioning
confidence: 99%
“…21 2. 2 22 About 5% of males aged >65 years who are current smokers have a >50% ICA stenosis on DUS screening 23 and smoking has been shown to increase plaque progression. 24 In a meta-analysis of 32 studies, smoking was associated with a significant increase in late ischaemic stroke (relative risk increase [RRI] 1.9, 95% CI 1.7e2.2).…”
Section: Recommendationmentioning
confidence: 99%
“…Although multiple imaging modalities are available, carotid duplex scanning has become a method of choice for preliminary investigation to assesses presence and severity of CAD, and in particular ICA stenosis. 13 Screening for carotid artery stenosis has not been proven a useful test in the general population. 14 Studies have shown that extracranial ICA stenosis is a risk factor for perioperative stroke in patients undergoing coronary artery bypass surgery.…”
mentioning
confidence: 99%